Clinical relevance of serum uric acid and abdominal aortic‐calcification in a national survey - Li, Yen‐Wei; Chen, Wei‐Liang (Clinical cardiology (Mahwah, N.J.), 2020)
Background Hyperuricemia was often found in subjects with an elevated risk of cardiovascular disease (CVD). Abdominal aortic‐calcification (AAC) is significantly associated with subclinical atherosclerotic disease. Hypothesis The aim of this study is to evaluate the relationship between serum uric acid (SUA) level and AAC from a national database. Methods A total of 2765 eligible participants older than 40 years who received dual‐energy X‐ray absorptiometry (DXA) scans with SUA data were enrolled from the National Health and Nutrition Examination Survey (2013‐2014). The association between SUA level and AAC was analyzed using multivariate regression models for covariate adjustment. Results After categorizing SUA level into four quartiles, the odds ratios for the presence of subclinical atherosclerosis via contrasting the highest SUA quartile with the lowest SUA quartile were 1.876 (95% CI = 1.298‐2.711), 2.038 (95% CI = 1.303‐3.187), 1.935 (95% CI = 1.221‐3.065), and 1.956 (95% CI = 1.225‐3.124) (all, P value less than .05) in Model 1, Model 2, Model 3, and Model 4, respectively. The above relationship remained still in the fully adjusted model for the male but not female subjects. The optimal SUA cutoff value was 6.35 mg/dL for male and 5.25 mg/dL for female to predict the presence of subclinical atherosclerosis. Conclusions Our results explore the promising evidences that SUA level showed a positive correlation with AAC score in a dose‐response manner. These findings decisively indicated that SUA may act as a promising tool to forecast the incidence of subclinical atherosclerosis in males.